Innovative Differentiated Learning for Inclusive Schools : Supporting Students with Special Needs - Mais, Asrorul; Yaum, Lailil Aflahkul (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
Abstract: This study aims to analyze differentiated learning innovations in the context of inclusive education. The main focus is how content, process and product differentiation strategies are implemented to accommodate student diversity and the role of Special Assistance Teachers (GPK) in supporting the learning of students with special needs. This study used a qualitative approach with a case study method. Data collection was carried out through observation, in-depth interviews, and document analysis. Research informants consisted of class teachers, GPK, madrasah principals, students, and parents. The data analysis technique used the Miles & Huberman interactive model, which includes data reduction, data presentation, concluding, and verification. The results of the study showed that content differentiation was implemented through various material formats, such as text, audio, and video, to accommodate diverse learning styles. Process differentiation was carried out using heterogeneous group-based learning methods and the use of teaching aids to improve student interaction and understanding. Meanwhile, product differentiation provides flexibility for students in displaying their understanding through various forms of assignments. Although this strategy increases student engagement and motivation, the main challenges found are limited resources, teacher readiness, and an evaluation system that does not fully support the differentiation approach. This study recommends increasing teacher training in differentiated learning strategies, optimizing the role of GPK, and utilizing educational technology to improve the effectiveness of inclusive learning.